2008
DOI: 10.1128/iai.01570-07
|View full text |Cite
|
Sign up to set email alerts
|

Galactose Residues on the Lipooligosaccharide ofMoraxella catarrhalis26404 Form the Epitope Recognized by the Bactericidal Antiserum from Conjugate Vaccination

Abstract: Lipooligosaccharide (LOS) fromMoraxella catarrhalis has the potential to elicit bactericidal antibodies against the pathogen. We generated LOS-based conjugate vaccines that elicited bactericidal antibodies in animal models. However, epitopes on the LOS recognized by the functional anti-LOS antibodies remain unidentified. In this study, a mutant strain, D4, which lost the recognition by a bactericidal anti-LOS rabbit serum in Western blotting was generated from a serotype C strain 26404 by random transposon mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…CE-ES-MS analysis of LPS-OH from the wild-type and mutant strains (Table 1) revealed that LPS-OH from the lgt2 mutant was 324.6 Da smaller than LPS-OH from the wild-type serotype A strain, corresponding to a loss of two hexoses, which is consistent with mutation of the lgt2 gene as previously shown [19]. LPS-OH from the lgt2/lgt4 mutant was 203.2 Da smaller than LPS-OH from the lgt2 mutant corresponding to a loss of an additional N-acetylhexosamine residue which is consistent with mutation of the lgt4 gene.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…CE-ES-MS analysis of LPS-OH from the wild-type and mutant strains (Table 1) revealed that LPS-OH from the lgt2 mutant was 324.6 Da smaller than LPS-OH from the wild-type serotype A strain, corresponding to a loss of two hexoses, which is consistent with mutation of the lgt2 gene as previously shown [19]. LPS-OH from the lgt2/lgt4 mutant was 203.2 Da smaller than LPS-OH from the lgt2 mutant corresponding to a loss of an additional N-acetylhexosamine residue which is consistent with mutation of the lgt4 gene.…”
Section: Resultssupporting
confidence: 81%
“…Previous studies on LPS based vaccines to combat M. catarrhalis have been carried out in the laboratories of Gu [13][14][15][16][17][18][19]. However the work of Gu has focused upon immunisation with conjugates derived from wild-type strains, thus raising the possibility of auto-immunity, and in the most recent paper indeed identified that the terminal galactose disaccharide, part of the pK antigen as the immunodominant epitope [19].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It is also important that this common LOS contains the ␣-D-Galp-(1-4)-␤-D-Galp moiety, which is involved in resistance to the bactericidal activity of human serum in one strain of M. catarrhalis (54). A recent investigation found that the loss of this same epitope decreased the recognition of bactericidal antibodies produced in mice against an M. catarrhalis conjugate vaccine (53). Our data suggest that some patients develop more antibodies to the terminal regions of M. catarrhalis LOS following infection; thus, the ␣-D-Galp- …”
Section: Resultsmentioning
confidence: 99%
“…Serotypes A and B are the predominant glycoforms expressed by most clinical isolates analyzed to date (12,46). In recently reported animal studies, other researchers suggested that detoxified M. catarrhalis LOS has potential as a vaccine antigen in a mouse pulmonary clearance model (16,19,52,53). While these data are both valuable and interesting, it is sometimes difficult to link observations of animals to those of humans (34).…”
mentioning
confidence: 99%